A comparative study of topical 10% KOH solution and topical 25% podophyllin solution as home-based treatments of molluscum contagiosum - Nameer K. Al-Sudany; Dler R. Abdulkareem (Wolters Kluwer Medknow Publications, 2016)
Background: Molluscum contagiosum is a common self-limiting viral infection of the skin. Many therapeutic agents have been used with varying success rates. Objective: To evaluate and compare the effectiveness of topical 10% KOH solution and 25% podophyllin solution as home-based treatments of molluscum contagiosum. Patients and methods: This open randomized comparative therapeutic trial was conducted in the department of dermatology, Al-Yarmouk Teaching Hospital, Baghdad, Iraq between January and October 2015. The patients were divided randomly into two equal groups. Group A patients were treated with 10% KOH solution and those in group B with 25% podophyllin solution. All patients were assessed weekly for 4 weeks for therapeutic response. Results: Fifty-two patients (age: 2-34 years) with MC were enrolled in this study, 25 patients in group A and 20 patients in group B completed the study. Sixteen (64%) patients in group A showed complete clearance of lesions versus 14 (70%) patients in group B. No systemic side effects were reported in both groups and the local side effects were comparable between both groups. Conclusion: Both 10% KOH solution and 25% podophyllin solution are effective local therapies for the treatment of MC with comparable success rates (64% and 70% respectively).